Com as linguagens, as crianças: brincadeiras na educação infantil - Faria, Paula Amaral (2020)
The present research is traversed by experiences of my life, some related to the arts, which allowed the constitution of the following queries: Why ac(know)ledge languages? Which types of language do children (re)produce in the school daily life? How are dialogs with children built and how are they expressed in the school daily life? What are the meanings and senses that children express in the daily life at school? From these questions, the objectives were: construct dialogs with the children at the child education school and understand how they practice types of language in the school daily life. Simultaneously with the experiences with the arts, I had contact with studies related to the school daily life which allowed me to learn about other ways of conducting research, especially a methodology woven in the own process of research from the relationships with the subjects of the investigation. This study was oriented by a qualitative perspective and inspired by ethnography principles; it was also based on cultural-historical psychology and on the sociology of childhood in order to discuss themes such as child, childhoods, types of language and the school daily life. The investigation was developed, from August to December 2017, at the child education municipal school (EMEI) Teacher Rosangela Borges Cunha, especially with the children, the educators and the teacher of the Class of Fish. I registered the daily life experienced at the school on field notes, analyzed them and selected meetings with the children so as to respond the questions presented. The analyses that I carried out are organized in three parts. In the first part, I (re)acknowledged the types of language practiced by the children, for example, speaking, gestures, dance, music, writing and drawing, highlighting the uses and reinventions that the children produced, especially when at play, indicating similarity to art. The potentiality of play in the child teaching-learning process was a big discovery. The second part of the analysis is subdivided in two: firstly, I found that thinking and language are constituted and expressed when at play through an interconnexion of imagination, emotion and gestures learned in cultures. Secondly, I discussed how art also composes the child learning process, constituting a complex language system. In the third part, I discussed how play proved to be an important way of communicating with the children at the child education school and understanding their needs, interests, meanings and senses articulated in the school daily life in the relationship teacher-student. I understood that teachers are fundamental in this process, and, for this reason, I signal to the relevance of qualification aimed at dialog, play and art in the relationship with children. Recognizing, valuing and promoting child practices of types of language in the school daily life consists of a political action of promoting an effective participation of children in the educational work and invites teachers to carry out sensitive and respectful educational actions to the discoveries of children and the several cultural manifestations.